Koko be good - Wang, Jen, 1984- (First Second, 2010)
"Koko's always got a new project cooking, even though they usually end in total disaster. This time will be different, Koko promises herself. This time, she's decided to Be Good. But how can a girl whose greatest talent is causing trouble get her act cleaned up? If she's being honest with herself, Koko isn't even sure what 'being good' means. Jon knows what being good means, and that's why he's going to Peru to support his girlfriend's humanitarian mission. That's good, all right, but is it what he wants? Jon has a promising future as a musician. Is he ready to give that up--maybe forever? Two very different people, both struggling for direction, find their way into each other's lives in Jen Wang's first graphic novel. Honest, wrenching, and incredibly funny, Koko Be Good is a tour-de-force debut about human nature and the inhuman efforts we make to find ourselves."--Publisher's Web site.